2016
DOI: 10.1186/s13075-016-0977-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported impact of spondyloarthritis on work disability and working life: the ATLANTIS survey

Abstract: BackgroundThe aim was to establish how patients experience the impact of spondyloarthritis (SpA) on work disability and working life.MethodsThe survey was performed in 17/20 regions in Italy (1 January to 31 March 2013). A multiple-choice questionnaire was published on the official website of the sponsor - the National Association of Rheumatic Patients (ANMAR) - and hard-copies were distributed at outpatient clinics for rheumatic patients.ResultsRespondents (n = 770) were of both sexes (56 % men), educated (62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 27 publications
5
38
0
Order By: Relevance
“…The prevalence of axSpA in Italy is 1.06 % [10] and the prevalence of nr-axSpA is estimated to be 0.35 % [11]. Few data on work productivity in Italian patients with axSpA are available [12]; it is therefore important to get a clear picture on how this disease impacts the work productivity. The aim of our study was to investigate work productivity and its relationship with disease activity and physical functioning in Italian patients with short-term chronic back pain (CBP) who participated in the Italian section of the Spondyloarthritis Caught Early (SPACE) cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of axSpA in Italy is 1.06 % [10] and the prevalence of nr-axSpA is estimated to be 0.35 % [11]. Few data on work productivity in Italian patients with axSpA are available [12]; it is therefore important to get a clear picture on how this disease impacts the work productivity. The aim of our study was to investigate work productivity and its relationship with disease activity and physical functioning in Italian patients with short-term chronic back pain (CBP) who participated in the Italian section of the Spondyloarthritis Caught Early (SPACE) cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of PsA and AxSpA on work productivity can be severe; an Italian survey sponsored by the National Association of Rheumatic Patients (ANMAR) revealed that over a third of patients with spondyloarthritis felt limited by their condition in their career progression and personal development [64]. In a large Swedish study of patients with spondyloarthritis, 45% reported reduced work productivity, with a mean reduction of 20% [65].…”
Section: Focusing On Patients' Priorities For Treatment Goalsmentioning
confidence: 99%
“…PsA is clinically heterogeneous; some patients have mild symptoms that may be limited to dactylitis alone or oligoarthritis, while others can have arthritis mutilans, a destructive form of arthritis leading to significant joint deformities . Despite recent advances in treatment, disability is still common, and half of patients with SpA reported disability in one recent survey of Italian patients …”
Section: Clinical Features and Epidemiology Of Ra Spa And Ici‐iamentioning
confidence: 99%
“…55 Despite recent advances in treatment, disability is still common, and half of patients with SpA reported disability in one recent survey of Italian patients. 56…”
Section: Disease Course and Prognosismentioning
confidence: 99%